2008
DOI: 10.1063/1.2937167
|View full text |Cite
|
Sign up to set email alerts
|

Mask pattern interference in AlGaInAs selective area metal-organic vapor-phase epitaxy: Experimental and modeling analysis

Abstract: We studied selective area growth modeling and characterization of the AlGaInAs material system. We used a three-dimensional vapor phase diffusion model to extract the effective diffusion lengths of Al, Ga, and In species from measured thickness profiles of the three binaries AlAs, GaAs, and InP. Our growth conditions yield to 50, 85, and 10 m for Al, Ga, and In, respectively. Based on these values, we achieved a precise prediction of AlGaInAs thickness, composition, band gap, and biaxial strain variations in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…1). The patterns were very long (900 mm) and sufficiently separated to avoid any influence on each other [4]. The different samples were selectively grown with various temperature and pressure conditions which will be described latter in the paper.…”
Section: Methodsmentioning
confidence: 99%
“…1). The patterns were very long (900 mm) and sufficiently separated to avoid any influence on each other [4]. The different samples were selectively grown with various temperature and pressure conditions which will be described latter in the paper.…”
Section: Methodsmentioning
confidence: 99%
“…A simple approach to model SAG is to consider only vapor phase diffusion (VPD) as the source material of supply. If no interaction is assumed between group III elements, each binary element can be considered to have an independent growth enhancement ratio that leads to identification of the composition and the growth enhancement ratio of the alloy in the vicinity of the mask [3].…”
Section: Photonic Integration Technologymentioning
confidence: 99%
“…Monolithic integration on InP is a way to facilitate the fabrication of complex Photonic Integrated Circuits (PIC) provided with multiple functions. We have sucessfully shown that InP actually provides the lowest-size full-monolithic transmitters (TX) for complex modulation formats (m-PSK, QAM etc) using a novel prefixed optical phase switching by low drive using EAM [3,4,5]. While keeping simple the transmitter and its driving electronics, it has the advantage over the more standard Pulse Amplitude Modulation (PAM) format to suppress the optical carrier and to provide better energy efficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…4,9,[13][14][15][16][17] Both situations involve gasphase diffusion and hence solutions of the Laplace equation, although in SAG the precursors are supplied at a plane located at a distance h above the wafer so that two dimensions are involved instead of one. In the numerical calculations growth was assumed to be diffusion-limited, and the results included numerical evaluation of the local gas-phase concentrations n͑r ជ͒ of the precursor within the stagnant layer and d as a function of r in the window region.…”
mentioning
confidence: 99%
“…These boundary conditions are used in the numerical simulations as well. 4,9,[13][14][15][16][17] We now project the concentration n͑x , y͒ of ͑a͒ into the ͑u , v͒ coordinate system. We use the transformation 21 a͒ Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%